Importance of vaccination within the integrated management of Rhipicephalus microplus in cattle (Revista Sistemas de Producción Agroecológicos, 2022)
The Rhipicephalus microplus complex is the most prevalent and best adapted in both tropical and subtropical areas, being the most important ectoparasite in cattle production in the world. It is imperative to join technical-scientific efforts to generate integrated management for this parasite, strategically reducing the use of conventional acaricides for its control, thus avoiding multi-resistant forms and evident alterations of safety in products of cattle origin, in addition harmful environmental impacts. Vaccination as a relevant control tool in integrated management of R. microplus is commercially available in Colombia, as in other countries of the American continent. Gavac™ from Cuba, Bovimune Ixovac® from Mexico and Go-Tick® from Colombia are tangible and widely validated vaccines to control the scourge of R. microplus and outbreaks of tick-borne diseases transmitted by this parasite, as well as to significantly reduce dependence on acaricides conventional. The results of the strategic structuring in the context of the integrated R. microplus management of detail important economic gains and ecological awareness.
Keywords: integrated R. microplus management; prophylaxis; reverse vaccinology